Experimental Transmission of Ulcerative Dermal Necrosis (UDN) from Affected to Healthy Sea Trout (Salmo trutta morpha trutta): Role of Environmental Factors in the Etiology of the Disease - Reichert, Michal; Matras, Marek; Stachnik, Magdalena; Kycko, Anna; Wasiak, Magdalena; Pazdzior, Ewa; Maj-Paluch, Joanna; Borzym, Ewa (Disease and Health Research: New Insights Vol. 8, 2024)
The aim of these in vivo experiments was to verify the possibility of transmission of the pathogen from ulcerative dermal necrosis (UDN)-affected fish to healthy fish. The NGS-based studies of nucleic acid samples from the UDN-affected fish tissues were performed using high-throughput sequencing on the Illumina platform followed by bioinformatics analysis. The serious losses of sea trout caused by the UDN threaten the preservation of the genetic resources of these valuable species. Every year, UDN attacks salmonids that spend most of their lives in the sea during their migration to the rivers of northern Poland to spawn. The clinical form of the disease manifests itself in ulcerative skin lesions, which lead to significant weakening of the fish and, in most cases, result in their death. The study was carried out on samples taken from sea trout in the Slupia River in northern Poland. In order to identify the pathogen, experiments on the transmission of the disease were carried out, as well as additional histopathological, microbiological, and electron microscopic examinations were performed. As a result of these studies, it was possible to experimentally transfer the disease from sick to healthy fish. The changes in the composition of mucus, as well as in the number of mucous cells in the skin, associated with the transition from the marine environment to freshwater, are accompanied by modifications of the structure of the epidermis in the form of damage or loss of micro-protrusions. The findings point to a complicated etiology for the illness (one without a well-defined pathogen), wherein the environmental shift from salt to freshwater and the ensuing modifications to skin physiology plays a major role in increasing susceptibility to the disease's development.